SOLUSI PROBLEM PENGHAPUSAN BUNGA DENGAN PENDEKATAN PRODUK BAI‘ BITSAMAN ĀJIL DALAM UPAYA MEWUJUDKAN LEMBAGA KEUANGAN LĀ-RIBA (Studi Kasus di BMT Damar dan BMT-KJKS IAIN Walisongo Semarang) - Siti Mujibatun (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2016)
Mudhārabah practices as an icon rather than LKS (Sharia Financial Institution) is still raise unresolved polemic associated with akunting system and balance, especially in the domain of financing, so that the stigma of people who think that the operating system is the same as the system of financial calculating interest only the different’s name has been continues. When examined in detail, there are other products that legitimized the contract either by the arguments Syara agreed by the majority of scholars and schools of jurisprudence, namely the contract of Ba‘i Bitsaman Ājil (BBA) or purchase by way of pay gradually. This article concludes; First, offers a BBA in finance BMT Damar and BMT-KJKS IAIN Walisongo experiencing significant growth, in addition to a simple transaction models are not complex, almost the akunting system likes fixed rate (fixed rate) so that customers become more familiar because the system is not much different from the credit money. Second, BBA financing acounting system can be separated from other products offered by BMT and not to be come one system with murābahah financing. Third, although the BBA acounting system similar to the system of interest and somewhat complicated because managers have the purchase to be come representer for wakālah contract to goods of customers, but offers and akunting BBA financing is more flexible and is not affected by rising interest rates as the often occurs in LKK )Conventional Financial Institutional)